Ethnoveterinary survey and laboratory evaluation of medicinal plants used for management of livestock respiratory and wound infections in Limpopo, South Africa - McGaw, Lyndy Joy (University of Pretoria, 2023)
Thesis (PhD)--University of Pretoria, 2022.